2004
DOI: 10.1051/0004-6361:20047173
|View full text |Cite
|
Sign up to set email alerts
|

A search for shock-excited molecular hydrogen knots in Chamaeleon I very low mass YSOs

Abstract: Abstract.We have obtained narrow-band images of three selected areas of the Chamaeleon I dark cloud which harbor very low mass young stars, centered on the H 2 and Brγ lines and neighboring continuum as well as on the broad band K s . One region is located in the northern part of the cloud, roughly coinciding with the densest area. The other two regions are in the southern section of the cloud. Our aim is to search for H 2 outflows associated with these objects. In the northern region, we found seven new H 2 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Although some shocks exhibit infrared emission in the IRAC bands, most notably HH 49/50 (the ''tornado''), most outflows in the Cha I clouds are not detected in the Spitzer IRAC bands. This result is consistent with the general lack of extensive 2.12 m emission from Cha I reported by Gómez et al (2004).…”
Section: Introductionsupporting
confidence: 92%
“…Although some shocks exhibit infrared emission in the IRAC bands, most notably HH 49/50 (the ''tornado''), most outflows in the Cha I clouds are not detected in the Spitzer IRAC bands. This result is consistent with the general lack of extensive 2.12 m emission from Cha I reported by Gómez et al (2004).…”
Section: Introductionsupporting
confidence: 92%
“…The three clouds have similar masses as traced with 13 CO 1−0 (∼1000 M ), but the fraction of denser gas traced with C 18 O 1−0 is the highest in Cha I (24%), while it is the lowest in Cha III (4%) (Mizuno et al 1999(Mizuno et al , 2001. Finally, several indications of jets/outflows were found in Cha I (Mattila et al 1989;Gómez et al 2004;Wang & Henning 2006;Belloche et al 2006). Only three Herbig-Haro objects are known in Cha II and none has been found in Cha III (Schwartz 1977).…”
Section: Introductionmentioning
confidence: 85%
“…Persi et al (1999), on the other hand, identified ISOCha I 192 as the driving source of a large-scale 12 CO (1-0) outflow in the region (Mattila et al 1989). Gómez et al (2004) found five H 2 knots that roughly align with the CO outflow direction.…”
Section: Introductionmentioning
confidence: 88%